Comparative analysis of transcriptome in oil biosynthesis between seeds and non-seed tissues of Symplocos paniculata fruit - Liu, Qiang; Chen, Yunzhu; Chen, Jingzhen; Li, Peiwang; Jiang, Lijuan; Li, Changzhu; Zeng, Wenbin; Yang, Yan (Frontiers in Plant Science, 2024)
The Symplocos paniculata, a woody oil plant, has garnered attention for its oil-rich fruit, which exhibits potential for both oil production and ecological restoration endeavors, thereby presenting substantial developmental value. However, the comprehension of the distinctive oil biosynthesis and deposition strategies within the fruit’s various compartments, coupled with the tissue-specific biosynthetic pathways yielding optimal fatty acid profiles, remains in its infancy. This investigation was designed to delineate the tissue specificity of oil biosynthetic disparities and to elucidate the molecular underpinnings within the fruit mesocarp and seeds of S. paniculata, employing lipidomic and transcriptomic analyses. The results revealed that oil biosynthesis within the fruit mesocarp commences approximately 40 days prior to that within the seeds, with a concomitant higher lipid content observed in the mesocarp, reaching 43% as opposed to 30% in the seeds. The fruit mesocarp was found to be enriched with palmitic acid (C16:0) and exhibited a harmonious ratio of saturated, monounsaturated, to polyunsaturated fatty acids (SFA: MUFA: PUFA=1:1:1), in stark contrast to the seed oil, which is predominantly composed of unsaturated fatty acids, accounting for 90% of its total FA content. Microstructural assessments have unveiled divergent oil deposition modalities; the fruit mesocarp oils are predominantly sequestered within oil cells (OC) and a spectrum of lipid droplets (LD), whereas the seeds predominantly harbor uniformly-sized LD. The expression patterns of pivotal genes implicated in oil biosynthesis were observed to be markedly contingent upon the tissue type and developmental stage. Notably, the light-responsive fatty acid synthase (FAS) gene demonstrated preferential transcription within the fruit mesocarp. In contrast, genes pivotal for carbon chain elongation, such as 3-ketoacyl-ACP synthase II (KASII) and fatty acyl-ACP thioesterase A (FATA), and desaturation, typified by Stearoyl-ACP desaturase (SAD) and Fatty Acid Desaturase (FAD), were noted to be more robustly transcribed within the seeds. Furthermore, isoenzyme gene families integral to the assembly of triacylglycerol (TAG), including long-chain acyl-CoA synthetases (LACSs), glycerol-3-phosphate acyltransferases (GPATs), and lysophosphatidic acid acyltransferases (LPATs), exhibited pronounced tissue specificity. This research endeavors to clarify the molecular regulatory mechanisms that oversee oil biosynthesis within both seed and non-seed tissues of oilseed-bearing plants with entire fruits. Collectively, these findings lay the groundwork and offer technical scaffolding for future targeted cultivation of woody oil plants, with the ultimate aim of augmenting fruit oil yield and refining FA compositions.